Four lichen species new to Spain - Crespo, Ana; Barreno, Eva; Sancho, Leopoldo G.; Pintado, Ana; Lumbsch, H. Thorsten (Lazaroa, 2003)
Four species of Lichens are reported as new to Spain, namely Aspicilia moenium, Lecanora stenotropa, Vezdaea leprosa and Xanthoparmelia plitii. The species are probably not rare, but overlooked, since they are either inconspicuous or morphologically similar to other species.